The Influence Of Discovery Learning Model Assisted By Audio-Visual Media On The Scientific Literacy Ability Of Fifth Grade Students At UPT SPF SDI BTN IKIP 1 Makassar - Nurhikmah, Nurhikmah; Irfan, Muhammad; Rahman, Abdul (International Journal of Elementary School Teacher, 2024)
This research aims to describe the application of the discovery learning model assisted by audio-visual media and the scientific literacy abilities of fifth-grade students, as well as the influence of the discovery learning model assisted by audio-visual media on the scientific literacy abilities of students in grade V at UPT SPF SD Inpres BTN IKIP 1 Makassar. The approach used in this research is a quantitative approach with a quasi-experimental type of non-equivalent control group design. The population in this study consisted of all fifth-grade students at UPT SPF SD Inpres BTN IKIP 1 Makassar. The sample consisted of 22 students from class VA and VB, selected using saturated sampling. Data collection techniques involved observation sheets and tests. The data analysis techniques used were descriptive and inferential statistical analysis. Descriptive analysis results show that the application of the discovery learning model assisted by audio-visual media went very well. Inferential analysis results using an Independent Sample t-Test showed a sig value of 0.012 < 0.05, meaning Ha was accepted, and Ho was rejected. Based on the results, it can be concluded that learning activities using the discovery learning model assisted by audio-visual media are very effective, the scientific literacy abilities of students improved after the implementation, and there is an influence of the model on the students' scientific literacy.